Reflexões sobre as macrotendências da educação ambiental presentes nas apostilas de sustentabilidade da Secretaria de Educação de Sorocaba: diálogos com a educação ambiental crítico-transformadora - Pedroso, Bruno Rodrigues (Universidade Federal de São Carlos, 2020)
The objective of this work is to reflect on the macro trends of environmental education (conservationist, pragmatic and critical) presented in the textbooks, having as object of study the sustainability handouts of the Sorocaba Municipal Secretariat of Education, used in the early years of elementary school. The methodology used for a qualitative analysis; documentary and bibliographic. The theoretical and methodological bases that inspire this work are from the macro trends of environmental education and of critical-transforming Environmental Education. The work highlights the role of Environmental Education: history, macro trends and hegemony, curricula and educational norms and category analysis. About the textbook, a survey addresses its history in Brazil, especially in the period of dictatorship until 2020, its financial, political, pedagogical and ideological costs. In the analysis of bankruptcy, the clipping of the booklet “Solid waste and consumption”, with the following categories of analysis: man's relations with nature, social equality, quality of life, raw materials and the State. We realize that the book is close to the pragmatic and conservationist view, as it aligns with aspects of individual blame, conservative values, individualistic and meritocratic attitudes, to the minimum state and generic solutions.
Reflections on the macrotendencies of environmental education present in the sustainability apostiles of the Sorocaba Education Secretariat: dialogues with critical-transforming environmental education
Keywords: Educação ambiental Crítico-transformadora. Macrotendências da Educação Ambiental. Livro didático; CIENCIAS HUMANAS::EDUCACAO::CURRICULO